RANCANG BANGUN APLIKASI POINT OF SALE (POS) BERBASIS WEB DENGAN PEMANFAATAN TRIGGER PADA DISTRIBUTION STORE CV. NMRQ - Hidayat, Dapai Ari (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2014)
One of the applications that can be developed and is a web-based Point of Sales (POS). A POS cash register system that can give information about the state of the store,  such as data management, transactions, reports, and events. The goal is to process sales data and the procurement of goods in stores and transaction reports to the profit and loss. On the other hand the system supports an additional feature of internal chat service to facilitate communication between central and branch. Trigger in the database is a key part in making this application. With the use of the trigger function in the database to facilitate application of the data accessed by multiple users in the  same time. If without using triggers in the database then the application will work harder than usual, especially for the process of adding inventory and sales. Therefore, the system built in database applications there is a trigger that simply call the trigger.